Newly Isolated High Squalene Producing Thraustochytrid Strain Aurantochytrium sp. P5/2 from Mangrove Habitats in Nakhon Si Thammarat Province, Thailand - MALAWET, Tarnhatai; BANGRAK, Phuwadol; PEERAPORNPISAL, Yuwadee; KAMLANGDEE, Niyom (Walailak Journal of Science and Technology (WJST), 2019)
Thraustochytrids are alternative potential sources of squalene, because they grow rapidly, are relatively easy to culture, and accumulate in large amounts. The objectives of this research were to isolate squalene-producing Thraustochytrids from fallen leaves in Paknakon Bay, including Paknakon Mangrove forest (N), Pakpanang Mangrove forest (P) and Thasala Mangrove forest (T), Nakhon Si Thammarat, Thailand, and to investigate their total lipid profile and squalene contents. A total of nine Thraustochytrid isolates were obtained.Morphological and molecular features revealed that those Thraustochytrids belonged to the genus Aurantiochytrium (N1, N14, P1/1, P5/2, P6/1, P43, T1, T26, and T42). Subsequently, they were cultivated and their cell dry weight, fatty acid compositions, and squalene contents were analyzed. At 96 h of cultivation, the dry cell weights ranged from 7.51 to 17.43 mg/g. The total lipid profile showed a broad spectrum of saturated fatty acids with an abundance of palmitic acid (16:0), 24.72 - 41.06 % TFA, pentadecanoic acid (15:0) 16.75 - 28.48 % TFA, heptadecanoic acid (17:0) 4.19 - 7.67 % TFA, lignoceric acid (24:0) 2.76 - 8.83 % TFA, myristic acid (14:0) 2.17 - 3.43 % TFA, stearic acid (18:0) 0.83 - 1.32 % TFA, arachidic acid (20:0) 0.19 - 0.33 % TFA, and behenic acid (22:0) 0.19 - 0.21 % TFA, respectively. Unsaturated fatty acids, including Docosahexaaenoic acid (22:6; 8.59 - 35.99 % TFA), Clupanodonic acid (22:5, 2.24 - 8.94 % TFA), Arachidonic acid (20:4, 0.32 - 0.60 % TFA), Eicosapentaenoic acid (20:5, 0.19 - 0.62 % TFA), Linolenic acid (18:3, 0.12 - 0.18 % TFA), and Erucic acid (22:1; 0.02 - 0.09 % TFA) were also found. The squalene contents ranged from 0.06 to 4.78 mg/g. The highest biomass and squalene-accumulation was achieved from strain P5/2, which was identified as Aurantiochytrium sp.ม with a maximum yield of 4.78 mg/g at 96 h of cultivation.